Impact of Production Technologies on Area and Productivity of Cashew in North Kerala - M.V. Sajeev, P.L. Saroj and Meera Manjusha A.V., (Indian Journal of Extension Education, 2018)
The study analyses the impact of production technologies on area, production and productivity of cashew inthe Kannur and Kasaragod districts of Kerala state, as a prerequisite for developing and initiating innovativetechnology interventions for combating low productivity and profitability from cashew cultivation. Resultsrevealed that highest area under cashew in farmer fields is occupied by the variety Priyanka followed byMadakkathara-2 with similar trend in adoption levels. The ‘Priyanka + Madakkathara - 2’ combination emergedto be the most popular one among farmers in the study area. Farmers realized highest production and productivityfrom variety Sulabha, followed by Madakkathara-2 and Priyanka. Correlation analysis showed that fourtechnologies; recommended varieties, planting and initial care, pruning and training and plant protection ashaving highly significant relationship with the cashew productivity achieved by farmers. The regression analysisidentified that increasing adoption of planting and initial care techniques, manures and fertilizers anddevelopment and popularization of user friendly plant protection measures can significantly increase the perunit productivity of cashew orchards in north Kerala. The study concludes that socio-economic and biophysicalfactors along with policy environment have a larger contribution in explaining cashew productivityand technology component alone cannot be expected to bring a positive impact. Understanding the abovedynamics in technology impact can help researchers and extension agencies working in cashew sector todesign better innovations and effective outreach strategies.